22.3k views
0 votes
Which phrase best describe the translation from the graph y = 2(x-15)^2+3 to the graph of y =2(x-11)^2+3?

User Kaya
by
5.6k points

2 Answers

3 votes

Answer:4 units to the left

Explanation:

User Shuntksh
by
5.6k points
2 votes

f(x - n) - shift the graph n units right

f(x + n) - shift the graph n units left

f(x) - n - shift the graph n units down

f(x) + n - shift the graph n units up

----------------------------------------------------------------------------

y = 2(x - 15)² + 3

y = 2(x -11)² + 3 = 2(x - 15 + 4)² + 3

Answer: shift the graph of y = 2(x - 15)² + 3 four units left.

User Elias Yarrkov
by
5.6k points